Missionær Jens Dixen og hedningemissionsforeningen »Libanon« - et dansk-amerikansk bidrag til dansk ydre missions historie - Jensen, Mogens (Kirkehistoriske Samlinger, 1992)
One of the main contributors to the foundation of the Sudan United Mission, Danish Branch, in 1911 was the Danish-American laypreacher and school-principal Jens Dixen. Having read about the endeavours of Rev. Anton Pedersen of Aalborg to create a mission society with Sudan as its working-field he donated about half of the amount necessary for the foundation of the society and created interest for mission in Africa among his students who as a result founded The Lebanon Society for that purpose. Jens Dixen was an outstanding person. Born in 0. Lindet in the then German part of Southern Jutland in 1858 he emigrated to America in 1880 and made his living there partly as a farmer, partly as a worker at the railway and later for many years as a ditch-digger. In 1889 he began as a lay-preacher among his countrymen and also as a schoolteacher during winter besides his job. In 1905 he was one of the originators of the Brorson Highschool in Kenmare, North Dakota, and its principal for nine years. As a lay-preacher Dixen travelled all over America visiting the Danish settlements, and four times he also travelled to Australia and New Zealand as a missionary to Danish emigrants there, always covering his own expenses. On his way to and from Australia/New Zealand he visited different missionfields in Africa and India getting an impression of the missionwork. From his early days Dixen had been interested in foreign mission especially in Africa. He was an active supporter of different societies, such as The China Inland Mission, The Alliance Mission, The Santal Mission, and he was the originator and first chairman of a society for foreign mission in The United Danish Evangelical Lutheran Church in North Dakota. In 1910 he participated in The World Missionary Conference in Edinburgh, and after that his eyes were again turned to Africa, so that when he read some articles about Sudan written by Rev. Anton Pedersen from Aalborg he was ready to support this work. Jens Dixens ecclesiastical background was highly interdenominational or maybe even better a-denominational. Being a lay-preacher and school-principal in a Lutheran Church this had to cause problems vis-àvis the Church. Another cause of problems was the Lebanon Society founded by Dixens pupils at the Brorson Highschool after his return from Edinburgh. Until its dissolution in 1934 its support to the Danish Sudan Mission which was not officially recognized by the Church from time to time created severe tensions. During the years the Lebanon Society supported 2 missionary couples at the Danish Field, both of the men previous students at Dixen’s school. Dixen himself returned with his wife, whom he had married in 1910, to Denmark in 1926 and continued as a lay-preacher almost to his death in January 1931 in Jels.